The social life of Scriptures : cross-cultural perspectives on biblicism - Bielo, James S. (Signifying (on) Scriptures., 2009)
The Social Life of Scriptures is the first book to present an eclectic, cross-cultural, and comparative investigation of Bible use. It models an important movement to outline a framework for how scriptures are implicated in organizing social structures and meanings, with specific foci on gender, ethnicity, agency, and power. Contributors offer a collection of closely analyzed and carefully conducted ethnographicand historical case studies, covering a range of geographic, theological, and culturalterritory.